2021
DOI: 10.1002/med.21866
|View full text |Cite
|
Sign up to set email alerts
|

The antiviral and immunomodulatory activities of propolis: An update and future perspectives for respiratory diseases

Abstract: Propolis is a complex natural product that possesses antioxidant, anti‐inflammatory, immunomodulatory, antibacterial, and antiviral properties mainly attributed to the high content in flavonoids, phenolic acids, and their derivatives. The chemical composition of propolis is multifarious, as it depends on the botanical sources from which honeybees collect resins and exudates. Nevertheless, despite this variability propolis may have a general pharmacological value, and this review systematically compiles, for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 212 publications
(461 reference statements)
0
22
0
Order By: Relevance
“…Various propolis extracts (e.g., aqueous, ethanolic, and hydroalcholic) at controllable laboratory condition have been found to exeret substantial antiviral activity against several types of viruses such as Herpes simplex virus type 1 and 2 (HSV-1 and HSV-2), Canine distemper virus, Human rhinovirus type 2, 3 and 4 (HRV-2, HRV-3 and HRV-4), Influenza virus type A and B, Parainfluenza virus, Human immunodeficiency virus (HIV), and Adenovirus [292,293].Research findings demonstrated that aqueous and ethanol propolis extracts exhibited a strong antiviral activity against HSV-1 [294] and HSV-2 [295] on RC-37 cells by affecting viral plaque formation and viral infection cycle. On the other hand, 0.5% aqueous extract of propolis showed potent antiviral activity against HSV-1 infected rats and rabbits thorough prevention of virus absorption into the host and inhibition of an internal step(s) during the viral replication cycle [296].…”
Section: Antiviral Activitymentioning
confidence: 99%
“…Various propolis extracts (e.g., aqueous, ethanolic, and hydroalcholic) at controllable laboratory condition have been found to exeret substantial antiviral activity against several types of viruses such as Herpes simplex virus type 1 and 2 (HSV-1 and HSV-2), Canine distemper virus, Human rhinovirus type 2, 3 and 4 (HRV-2, HRV-3 and HRV-4), Influenza virus type A and B, Parainfluenza virus, Human immunodeficiency virus (HIV), and Adenovirus [292,293].Research findings demonstrated that aqueous and ethanol propolis extracts exhibited a strong antiviral activity against HSV-1 [294] and HSV-2 [295] on RC-37 cells by affecting viral plaque formation and viral infection cycle. On the other hand, 0.5% aqueous extract of propolis showed potent antiviral activity against HSV-1 infected rats and rabbits thorough prevention of virus absorption into the host and inhibition of an internal step(s) during the viral replication cycle [296].…”
Section: Antiviral Activitymentioning
confidence: 99%
“…e honeybee products like honey, beeswax, bee venom, and bee pollen have been used as traditional medicine and also exhibited antimicrobial, antioxidant, anti-inflammatory, and anticancer properties in several preclinical studies in cell line and animal experiments [13][14][15][16][17]. e word "Propolis" comes from Greek that means defense for "pro" and city or community for "polis," or the beehive in other words.…”
Section: Propolismentioning
confidence: 99%
“…Flavonoids have been widely utilized in traditional medical practices to combat bacterial infections [17,399,400] with some approaches focusing specifically on how to combat MDR bacteria [400][401][402][403][404]. Combination therapies with antibiotics [405] and approaches examining how the antiviral and immunomodulatory properties of flavonoids can be harnessed in the treatment of respiratory diseases have also been examined [406].…”
Section: Bacterial Infections Associated With Long Covid Diseasementioning
confidence: 99%